Reduction of magnetic resonance image artifacts of NiTi implant by carbon coating - Han, Taeyang; Sohn, Youhan; Park, Sang Jin; Kim, Yu-Chan; Lee, Kang Sik; Kim, Hye Sung; Yoon, Soon-Gil; Kim, Dojin; Han, Jun Hyun (Elsevier BV, 2019)
A paramagnetic NiTi substrate was coated with diamagnetic carbon materials, i.e., graphene, graphene oxide (GO), and carbon nanotubes (CNTs), in order to reduce magnetic resonance (MR) image artifacts of NiTi implants. The present study focused on the effect of magnetic susceptibility variations in NiTi caused by the carbon coating on MR image artifacts. In the case of the graphene and GO coatings, the reduction of the magnetic susceptibility was greater along the perpendicular direction than the parallel direction. In contrast, the CNT coating exhibited a larger reduction along the parallel direction. The reduction of magnetic susceptibility measured in CNT-coated NiTi (CNT/NiTi) was smaller than the theoretical prediction especially when measured along the parallel direction, because CNTs on the NiTi surface were randomly arranged, rather than in a single direction. MR image artifacts were substantially reduced in all carbon-coated NiTi specimens, which is due to the reduction of magnetic susceptibility in NiTi by the carbon coating. This method can also be applied to other paramagnetic bio-metallic materials such as Co-Cr.
Keywords: SUSCEPTIBILITY ARTIFACTS; MR ARTIFACTS; SPIN-ECHO; GRAPHENE; COMPATIBILITY